Decaying Raphia farinifera Palm Trees Provide a Source of Sodium for Wild Chimpanzees in the Budongo Forest, Uganda - Reynolds, Vernon; Lloyd, Andrew W.; Babweteera, Fred; English, Christopher J. (PloSone, 2009)
For some years, chimpanzees have been observed eating the pith of decaying palm trees of Raphia farinifera in the Budongo Forest, Uganda. The reasons for doing this have until now been unknown. An analysis of the pith for mineral content showed high levels of sodium to be present in the samples. By contrast, lower levels were found in bark of other tree species, and also in leaf and fruit samples eaten by chimpanzees. The differences between the Raphia samples and the non-Raphia samples were highly significant (p,0.001). It is concluded that Raphia provides a rich and possibly essential source of sodium for the Budongo chimpanzees. Comparison of a chewed sample (wadge) of Raphia pith with a sample from the tree showed a clear reduction in sodium content in the chewed sample. Black and white colobus monkeys in Budongo Forest also feed on the pith of Raphia. At present, the survival of Raphia palms in Budongo Forest is threatened by the use of this tree by local tobacco farmers.
Keywords: Decaying Raphia farinifera Palm Trees; Sodium; Wild Chimpanzees; Budongo Forest; Uganda